Electrochemical Techniques in Textile Processes and Wastewater Treatment - Mireia Sala; M. Carmen Gutiérrez-Bouzán (International Journal of Photoenergy)
The textile industry uses the electrochemical techniques both in textile processes (such as manufacturing fibers, dyeing processes, and decolorizing fabrics) and in wastewaters treatments (color removal). Electrochemical reduction reactions are mostly used in sulfur and vat dyeing, but in some cases, they are applied to effluents discoloration. However, the main applications of electrochemical treatments in the textile sector are based on oxidation reactions. Most of electrochemical oxidation processes involve indirect reactions which imply the generation of hypochlorite or hydroxyl radical in situ. These electrogenerated species are able to bleach indigo-dyed denim fabrics and to degrade dyes in wastewater in order to achieve the effluent color removal. The aim of this paper is to review the electrochemical techniques applied to textile industry. In particular, they are an efficient method to remove color of textile effluents. The reuse of the discolored effluent is possible, which implies an important saving of salt and water (i.e., by means of the “UVEC Cell”).